PENGARUH PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR MATEMATIKA MATERI BARISAN DAN DERET BILANGAN - Wenas, John Robby; Regar, Vivian; Pontomudis, Hary (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
Abstract.  This research aims to determine the students learning outcomes taught using the Teams Games Tournament model and those using the conventional model on line and number sequence lesson. The research is categorized as quasi experiment. This research was conducted at SMPN 16 SATAP Bitung during the odd semester of the 2019/2020 academic year. The subject in this research were students of class IX-A as an experimental class and students of class IX-B as a control class. Data of the learning outcomes  were colectd with a test, and were analyzed using the t-test statistic. The results show that the average of the students learning outcomes taught using the Teams Games Tournament model were more than the average of the students learning outcome taught using conventional models on line and number sequence lesson. Key Words: Conventional, Learning Ontcomes,  Teams Games Tournament